Promotion and implementation effectiveness of World Health Organization's Caregiver Skills Training program in Taiwan - Seng, Guan-Jye; Chiu, Yen-Nan; Tsai, Wen-Che; Lin, Hsiang-Yuan; Li, Su-Chen; Hsiao, Mei-Ni; Liu, Tseng-Jung; Chen, Heng-Man; Shih, Andy; Chang, Ya-Chih; WHO CST Team,; Soong, Wei-Tsuen (Frontiers in Psychiatry, 2022)
The World Health Organization (WHO) and Autism Speaks developed the Caregiver Skills Training Program for Children with Developmental Disorders or Delays (CST) to address the resource gaps and worldwide needs for interventions for children with developmental disorders or delays, especially those with autism spectrum disorder (ASD), and their families. Evidence has indicated that parent-mediated interventions benefit both caregivers and children by strengthening caregivers’ knowledge and confidence and children’s social communication skills and behavioral regulation. The CST-Taiwan team began the prepilot field trial in 2017 and developed the project to serve families in various locations. This study (1) delineated the adaptations and promotion of CST-Taiwan; (2) determined the program’s effectiveness in the promotional stage, in terms of caregiver and child outcomes, and (3) examined the maintenance of its effects. The content, delivery, and facilitator training procedure of the original CST were adapted to Taiwan. The quantitative data indicated that CST-Taiwan is a promising program, it positively affected caregiver knowledge and confidence and reduced the severity of the children’s autistic symptoms. The 3-month follow-up results suggested that the effects persisted. Thus, CST-Taiwan, and its promotional strategies are feasible and effective.